2011
DOI: 10.1002/gea.20346
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface weathering on the geochemical analysis of archaeological lithic samples using non‐destructive polarized energy dispersive XRF

Abstract: The purpose of this paper is to show the effects of lithic artifact surface weathering on whole rock non-destructive polarized energy dispersive X-ray fluorescence (P-ED-XRF) major and trace element determinations. Chemical results for a weathered and subsequently mechanically ground subset of New Hampshire Ossipee archaeological flakes, cataloged as hornfels, show that both groups of elements are variably affected by weathering. A graphic approach is developed and proposed to highlight the role and importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…The method used in this study was developed at the Laboratoire de Caractérisation des Matériaux Archéologiques, Université de Montréal laboratory and is fully described in Gauthier and Burke (2011).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The method used in this study was developed at the Laboratoire de Caractérisation des Matériaux Archéologiques, Université de Montréal laboratory and is fully described in Gauthier and Burke (2011).…”
Section: Methodsmentioning
confidence: 99%
“…The same chemical element can play different roles in a mineral lattice; it can act as a network former in one type of mineral and fill the interstices in another type thus affecting its mobility. Gauthier and Burke (2011) have clearly shown that the effects of weathering on the non-destructive ED-XRF geochemical analysis of a weathered subset of New Hampshire Ossipee archaeological andesite flakes are considerable. The quartz dominant mineralogy of chert is expected to be more resistant to weathering than that of andesite, a ferromagnesian rich volcanic rock.…”
Section: Geochemical Effects Of Weatheringmentioning
confidence: 98%
See 3 more Smart Citations